2005
DOI: 10.1007/s00709-004-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Plastid stromules: video microscopy of their outgrowth, retraction, tensioning, anchoring, branching, bridging, and tip-shedding

Abstract: Stromules are stroma-containing tubules which can grow from the surface of plastids, most commonly leucoplasts and chromoplasts, but also chloroplasts in some tissues. Their functions are obscure. Stills from video rate movies are presented here. They illustrate interaction of stromules with cytoskeletal strands and the anchoring of stromules to unidentified components at the cell surface. Anchoring leads to stretching and relaxation of stromules when forces arising from cytoplasmic streaming act on the attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
137
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 14 publications
7
137
0
2
Order By: Relevance
“…In cinephotomicrographic and video microscopic studies, chloroplast protuberances have been observed to segment into vesicular structures (Wildman et al, 1962;Gunning, 2005). The release of bodies approximately 1.5 mm in diameter from the ends of stromules has been observed (Gunning, 2005). In transgenic plants expressing stroma-targeted GFP, GFP bodies of similar size, which are presumably separated from plastids or stromules, have also been observed by LSCM (Arimura et al, 2001;Waters et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In cinephotomicrographic and video microscopic studies, chloroplast protuberances have been observed to segment into vesicular structures (Wildman et al, 1962;Gunning, 2005). The release of bodies approximately 1.5 mm in diameter from the ends of stromules has been observed (Gunning, 2005). In transgenic plants expressing stroma-targeted GFP, GFP bodies of similar size, which are presumably separated from plastids or stromules, have also been observed by LSCM (Arimura et al, 2001;Waters et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…In cinephotomicrographic and video microscopic studies, chloroplast protuberances have been observed to segment into vesicular structures (Wildman et al, 1962;Gunning, 2005). The release of bodies approximately 1.5 mm in diameter from the ends of stromules has been observed (Gunning, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Time-lapse movies using differential interference contrast microscopy suggested that the sporadically extending and retracting tubules could result in plastid interactions. 6 However, it was the discovery of the green fluorescent protein (GFP) and its subsequent targeting to the plastid stroma that clearly highlighted fluorescent tubules and resulted in the coining of a simple descriptive term 'stromule' by Kohler and Hanson. 4,5 Further, GFP photo-bleaching showed that there is a flow and exchange of macromolecules between interconnected plastids.…”
mentioning
confidence: 99%
“…4,7,8 Since their re-discovery numerous conditions leading to stromule induction have been reported in original publications and discussed in several reviews. [5][6][7][8][9][10][11][12][13][14] The authoritative review by Hanson and Sattarzadeh 12 specifically appraised the status of stromules and provided a balanced discussion on the different possible roles that stromules might play within the cell. Most importantly this review clearly states that "most plastids are not connected at any one time, although over the course of a day, it is possible that many plastids within a cell establish transient contacts through stromules".…”
mentioning
confidence: 99%
See 1 more Smart Citation